The Ketogenic Diet in the Treatment of Post-concussion Syndrome—A Feasibility Study - Rippee, Michael; Chen, Jamie; Taylor, Matthew (Frontiers in Nutrition, 2020)
Concussion is the most common form of mild traumatic brain injury (mTBI). Although most patients’ symptoms resolve within a month, patients with post-concussion syndrome (PCS) may continue to experience symptoms for years and have limited treatment options. This pilot study assessed the feasibility and symptom-related effects of a ketogenic diet (KD) in patients with PCS symptoms. The Ketogenic Diet in Post-Concussion Syndrome (KD-PCS) was a single-arm trial of a 2-month KD high in non-starchy vegetables and supplemented with medium-chain triglyceride (MCT) oil. Macronutrient targets were ≥70% fat, ≤10% carbohydrate, and the remainder as protein as energy. We assessed feasibility by daily self-reported measure of urine acetoacetate and collection of 3-day food records and serum beta-hydroxybutyrate at multiple timepoints. We assessed symptoms by administering the Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) and Modified Balance Error Scoring System (M-BESS) at baseline and month 2 and the Post-Concussion Symptom Scale (PCSS) at baseline, month 1, and month 2. Fourteen participants enrolled in the KD-PCS. Twelve participants completed the study and 11 implemented the KD (73% fat, 9% carbohydrate, and 18% protein) and achieved ketosis. One participant complained of MCT-related diarrhea that resolved and another reported nausea and fatigue that resulted in withdrawal from the study. Among compliant participants, the visual memory domain of the ImPACT improved by 12 points (p=0.02) and PCSS scores improved by 9 points, although not statistically significant. This pilot trial suggests that the KD is a feasible experimental treatment for PCS and justifies further study of its efficacy.